2017
DOI: 10.3324/haematol.2016.163022
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetically induced ectopic expression of UNCX impairs the proliferation and differentiation of myeloid cells

Abstract: We here describe a leukemogenic role of the homeobox gene UNCX, activated by epigenetic modifications in acute myeloid leukemia (AML). We found the ectopic activation of UNCX in a leukemia patient harboring a t(7;10)(p22;p14) translocation, in 22 of 61 of additional cases [a total of 23 positive patients out of 62 (37.1%)], and in 6 of 75 (8%) of AML cell lines. UNCX is embedded within a low-methylation region (canyon) and encodes for a transcription factor involved in somitogenesis and neurogenesis, with spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…Local recurrence and distant metastasis are the major patterns of treatment failure in NPC. Most cancers are caused by accumulation of genomic or epigenetic alterations [ 19 24 ], and epigenetic alterations play an important role in the development of NPC [ 9 , 25 ]. Several studies have indicated that aberrantly methylated genes could serve as prognostic biomarkers for NPC [ 26 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Local recurrence and distant metastasis are the major patterns of treatment failure in NPC. Most cancers are caused by accumulation of genomic or epigenetic alterations [ 19 24 ], and epigenetic alterations play an important role in the development of NPC [ 9 , 25 ]. Several studies have indicated that aberrantly methylated genes could serve as prognostic biomarkers for NPC [ 26 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A central role in the repression of Uncx expression in the anterior somite is played by a complex regulatory network that involves the basic helix–loop–helix transcription factor Mesp2, its downstream co-repressor Ripply, the homeodomain transcription factor MEOX1, and a cross-negative regulation with the T-box protein Tbx18 (Takahashi et al, 2000, Takahashi et al, 2003, Takahashi et al, 2013; Nakajima et al, 2006; Farin et al, 2008; Skuntz et al, 2009; Yabe et al, 2016). Recently, cell type-specific epigenetic regulation of Uncx gene expression has been associated with axon guidance in C. elegans (Zheng et al, 2013) and with human leukemia (Daniele et al, 2017). It has been proposed that Uncx is implicated in cell cycle progression of neuronal progenitor cells, survival of olfactory epithelium and differentiation of dopaminergic neurons (Sammeta et al, 2010; Rabe et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…UNCX was another gene with distinct expression distribution between training and validation data. It is a homeobox transcription factor that has been associated with acute myeloid leukemia ( Daniele et al, 2017 ). MAMDC2 is a known tumor suppressor involved in glycosaminoglycan binding ( Lee et al, 2020 ), whereas NPIPB6 has not previously been associated with cancers to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%